The influence of role models in undergraduate nurse education. Issue 23 (19th May 2017) - Jack, Kirsten; Hamshire, Claire; Chambers, Alison
Abstract : Aims and Objectives: To explore the concept of role modelling in undergraduate nurse education and its effect on the personal and professional development of student nurses. Background: Effective educative strategies are important for student nurses, who have to cope with learning in both clinical and university settings. Given the contemporary issues facing nurse education and practice in the United Kingdom (UK), it is timely and important to undertake pedagogical research into the concept of role modelling as an effective educative method. Design: A descriptive narrative approach. Methods: Unstructured interviews were conducted with 14 current/recently discontinued students from Adult and Mental Health branches of nursing degree programmes in the north‐west region of England, United Kingdom (UK). Data were thematically analysed. Results: Students valued exposure to positive role models in clinical and university settings and viewed them as beneficial to their learning. Exposure to negative role models occurred, and this provided students with opportunities to consider the type of nurse they aspired to become. In some cases, students' exposure to perceived poor practice had an adverse effect on their learning and led to negative feelings about nursing work. Clinical staff might be perceived as more relevant role models than those in the university setting although there were still opportunities for academic staff to model professional behaviours. Conclusion: The study found that role modelling is an effective way to support learning and led to student satisfaction across both clinical and university settings. The findings support the use of role models in nurse education, and further research about conscious positive modelling of practice is required. Relevance to practice: Exploring the use of role models is important when examining ways in which the quality of nurse education might be developed.